2020
DOI: 10.1111/ppc.12583
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in the postpartum period: Its relationship with postpartum depression and certain other factors

Abstract: Purpose: This study aimed to determine the prevalence of female sexual dysfunction in the postpartum period and its relationship with postpartum depression and certain other factors.Design and Methods: Data were collected using an information form, the female sexual function index (FSFI), and the Edinburgh postpartum depression scale (EPDS) (N = 123).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
(23 reference statements)
0
7
0
2
Order By: Relevance
“…In the study by Quoc Huy et al, women over the age of 30 had a higher risk of FSD, which could be attributable to the progressive fall in estrogens occurring in the gradual hormonal change which women experience as they get older [ 34 ]. In other studies, a higher risk of FSD was found in women aged 35 and over [ 29 ]. Parity is another variable analyzed in the present study, and despite not appearing as a factor associated with the risk of FSD in the RLM model, significant differences were found in terms of greater communication disorders in multiparous women; some authors have linked primiparity with a higher risk of FSD [ 15 , 34 ], although others have found a higher risk in multiparous women [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the study by Quoc Huy et al, women over the age of 30 had a higher risk of FSD, which could be attributable to the progressive fall in estrogens occurring in the gradual hormonal change which women experience as they get older [ 34 ]. In other studies, a higher risk of FSD was found in women aged 35 and over [ 29 ]. Parity is another variable analyzed in the present study, and despite not appearing as a factor associated with the risk of FSD in the RLM model, significant differences were found in terms of greater communication disorders in multiparous women; some authors have linked primiparity with a higher risk of FSD [ 15 , 34 ], although others have found a higher risk in multiparous women [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 85%
“…In other studies, a higher risk of FSD was found in women aged 35 and over [ 29 ]. Parity is another variable analyzed in the present study, and despite not appearing as a factor associated with the risk of FSD in the RLM model, significant differences were found in terms of greater communication disorders in multiparous women; some authors have linked primiparity with a higher risk of FSD [ 15 , 34 ], although others have found a higher risk in multiparous women [ 26 , 29 ]. Although, in the present study, the level of self-esteem was not a variable associated with the risk of FSD according to the RLM model, we did find a higher percentage of alterations in general sexual satisfaction in women with a medium-low level of self-esteem.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Los problemas sexuales posparto son muy frecuentes 9,10,26 . En este estudio, de las mujeres sexualmente activas y sin dificultades sexuales antes del parto, casi la mitad refirió algún grado de deterioro de su vida sexual después del parto, lo que sugiere una evidente relación entre el parto y el deterioro de la función sexual; datos acordes con lo expresado en otras publicaciones 29,30 .…”
Section: Discussionunclassified
“…17% in Japan, 23.2% in China, 17.8% in the United Arab Emirates, 1% in Iceland 14, PPD prevalence was reported as 12.7% in Sweden, 12% in England, 6.5-12.9% in Norway, and 15.5% in Sri Lanka (Ahmed et al, 2021;Qi et al, 2021). In studies conducted in Turkey, the frequency of PPD is within a broad perspective of 23.8-61.8% (Ahmed et al, 2021;Dağlı et al, 2021). Therefore, it would be meaningful to examine birth satisfaction specifically for Turkish women.…”
Section: Introductionmentioning
confidence: 98%